Quantum random number generator using a microresonator-based Kerr oscillator - Okawachi, Yoshitomo; Yu, Mengjie; Luke, Kevin; Carvalho, Daniel O. [UNESP]; Lipson, Michal; Gaeta, Alexander L. (Optica Publishing Group, 2016)
We demonstrate an all-optical quantum random number generator using a dual-pumped degenerate optical parametric oscillator in a silicon nitride microresonator. The frequency-degenerate bi-phase state output is realized using parametric four-wave mixing in the normal group-velocity dispersion regime with two nondegenerate pumps. We achieve a random number generation rate of 2 MHz and verify the randomness of our output using the National Institute of Standards and Technology Statistical Test Suite. The scheme offers potential for a chip-scale random number generator with gigahertz generation rates and no postprocessing.